Cytotoxicity test of apple cider vinegar as a root canal irrigant against fibroblast cells - Lesmana, Sylvia Bunga; Djuanda, Rudy; Sugiaman, Vinna Kurniawati (Odonto : Dental Journal, 2022)
Background: Apple cider vinegar potentially can be used as an alternative to irrigation solutions because of its antibacterial compounds that can inhibit Enterococcus faecalis, a pioneer bacteria that cause root canal treatment failure. One of the ideal irrigation solution requirements is that it isn’t toxic to oral cavity tissues, so it’s necessary to run a cytotoxicity test on apple vinegar solution. Cytotoxicity test is the initial part of the evaluation of a dental material before it can be used by humans. Cytotoxicity test was performed on fibroblast cells because the irrigation solution can contact with fibroblast, which are the main cells in the periodontal ligament around the apical. The purpose of this study was to analyze the in vitro cytotoxicity effect of ACV on fibroblast cells.Method: Apple vinegar with concentrations of 0.31%, 0.63%, 1.25%, 2.5%, and 5% was tested using the MTS assay method.Result: The results showed that there was a cytotoxicity effect of apple vinegar solution as a root canal irrigation agent against fibroblasts cell. Apple cider vinegar with concentrations of 1.25%, 2.5%, and 5% are potentially toxic because the percentage of cell viability is less than 70%.Conclusion: There is a cytotoxicity effect of apple cider vinegar solution as a root canal irrigant on fibroblast cells